Studi Komparatif Efisiensi Biaya Sistem Rafter Baja Untuk Gudang Di Padang Sumatera Barat - Maulani, Febiana; Guci, Jeply Murdiaman; Maharani, Dwi Jenita (Universitas Andalas, 2025)
Cost efficiency is one of the considerations in material selection in construction. This study compares and analyzes the cost efficiency of three steel rafter systems, namely Wide Flange (WF), Castellated Beam, and Truss for warehouse construction in Padang City. The rafter structure design uses the design in previous studies. Based on the calculation of material volume and analysis of HSP Field of PU-AN and SHSTBGN in 2025, the rafter with the Truss system shows significant cost advantages with savings reaching 15.17% compared to WF and 10% compared to Castellated Beam. Calculations show that the weight of the Truss material is only 73.24 kg/m with a cost of Rp 994,254,600, more economical than WF (90.27 kg/m, Rp 1,172,112,500) and Castellated Beam (79.34 kg/m, Rp 1,053,917,100). The cost efficiency of Truss is not only in material savings, but also in reducing structural loads. Despite higher fabrication costs, resulting in the highest unit price for trusses, a total cost analysis shows that trusses remain the most economical option for warehouse projects in Padang. These findings provide practical guidance for contractors in selecting the optimal rafter system to reduce construction costs without sacrificing structural quality.